Development of a Traffic Light Control System Using ARM-Based Microcontroller - Mohd Zaki, Muhammad Asyraf Hakim; Chua, King Lee; Chia , Kim Seng (Evolution in Electrical and Electronic Engineering, 2026)
Traffic lights are widely used at road intersections to regulate vehicle movement through red, yellow, and green signals. However, the absence of a clear time indication for each phase can cause driver uncertainty, sudden braking, and red-light violations. To address these issues, this project develops a traffic light control system with a single countdown timer as an indicator to road users while reducing implementation costs and simplifying hardware interconnections. The system is divided into two main parts: software development and hardware implementation. The C programming language is used to compute the traffic control program. The program is written, tested, debugged, and then programmed onto the NXP LPC1768 development board using the Keil uVision Integrated Development Environment (IDE). The developed program controls the timing sequence of the traffic lights, manages the countdown display, and determines the pedestrian crossing phase according to a predefined fixed-time schedule. The hardware part involves assembling components such as 7-segment displays, Light-Emitting Diode (LED) traffic lights, and the microcontroller development board. The traffic light system is designed to implement a 30s green light phase, followed by yellow and red light phases. During the final 10s, the countdown from 9 to 0 is displayed using a single 7-segment. In addition, a dedicated pedestrian crossing phase is activated at the end of each full cycle, during which all vehicle signals are red to allow pedestrians to cross safely. The project demonstrates a fully functional traffic control system with an effective countdown display and smooth integration of the software and hardware components. The novelty of this project is a low-cost traffic control system that uses a single 7-segment display for the countdown phase, which reduces hardware cost, simplifies the circuit design, and cutting required microcontroller pins.